Analisis Faktor Faktor Yang Mempengaruhi Pengangguran Terdidik Di Sumatera Barat - Reza Tri Ananda; Ariusni (Universitas Negeri Padang, 2026)
This research aims to assess the effect of economic factors on the level of educated unemployment in West Sumatra Province. Educated unemployment is defined as individuals who have completed secondary or higher education but have not yet secured employment. The independent variables analyzed in this study include economic growth, the Human Development Index (HDI), population size, and employment opportunities. The study utilizes panel data covering 19 districts and cities over the period from 2014 to 2023. The analytical method employed is panel data regression using the Fixed Effect Model (FEM). The results reveal that economic growth, population size, and employment opportunities have a negative and significant influence on educated unemployment. This indicates that increases in these variables tend to lower the unemployment rate among educated individuals. In contrast, the HDI exhibits a positive but statistically insignificant effect, suggesting that improvements in quality of life have not yet directly contributed to reducing unemployment